2007
DOI: 10.1111/j.1467-9841.2007.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Talkin' Jockney’? Variation and change in Glaswegian accent1

Abstract: This paper presents an analysis of language variation and change in a socially stratified corpus of Glaswegian collected in 1997. Eight consonantal variables in read and spontaneous speech from 32 speakers were analysed separately and then together using multivariate analysis. Our results show that middle-class speakers, with weaker network ties and more opportunities for mobility and contact with English English speakers, are maintaining traditional Scottish features. Working-class adolescents, with more limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 26 publications
3
89
0
Order By: Relevance
“…Rather our conservative statistical treatment of the data showed consistent tendencies, with a few statistically significant instances, for the inference of real-and apparent-time lengthening of VOT in voiced and voiceless stops in all groups of speakers bar those born in the 1990s and recorded in the 2000s, who show shorter VOT durations, even controlling for speech rate. This last group has also been observed to be reverting to more non-standard vernacular norms, both local and non-local, for other phonological features (e.g., Stuart-Smith et al 2007). The use of stops with shorter VOT, more usually associated with vernacular Scots, may be part of a more general construction of local, nonstandard sociolinguistic personae.…”
Section: Discussionmentioning
confidence: 99%
“…Rather our conservative statistical treatment of the data showed consistent tendencies, with a few statistically significant instances, for the inference of real-and apparent-time lengthening of VOT in voiced and voiceless stops in all groups of speakers bar those born in the 1990s and recorded in the 2000s, who show shorter VOT durations, even controlling for speech rate. This last group has also been observed to be reverting to more non-standard vernacular norms, both local and non-local, for other phonological features (e.g., Stuart-Smith et al 2007). The use of stops with shorter VOT, more usually associated with vernacular Scots, may be part of a more general construction of local, nonstandard sociolinguistic personae.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also examined the role of the media on representation and recognition of geographical areas (for example Bayard, 1990;Goodey, 1973;Montgomery and Beal, 2011;Stuart-Smith, Timmins & Tweedie, 2007). However, the East Midlands region lacks TV representation.…”
Section: The East Midlandsmentioning
confidence: 99%
“…Previous research on Glaswegian has shown that production of a range of consonants is strongly stratified by social class (e.g. Stuart-Smith et al 2007), with innovative variants being particularly common among working-class adolescents in the core period of adolescence (aged 13-15 years old). We have also found variation according to ethnicity, including ejectives in read speech in Glaswegian Asian speakers (Lambert et al 2007).…”
Section: What Social Factors Constrain Ejective Use?mentioning
confidence: 99%
“…Glasgow is the largest city in Scotland and one that has suffered from the decline of heavy industry, but at the same time it has seen substantial urban regeneration and economic revival (see e.g. StuartSmith, Timmins & Tweedie 2007). Scottish English comprises a range of varieties along a sociolinguistic continuum.…”
Section: Samplementioning
confidence: 99%